Innovation in higher education : commemorative summary of panel presentations of the international seminar on innovation in higher education - Fernández, Celestino (CETYS Universidad, 2017)
Experts from UNESCO (Rethinking Education, 2015) say that the debate about education is centered around three questions: What education do we need for the 21st century? What is the purpose of education in the current context of societal transformation? How should learning be organized? These questions remain appropriate when taken into the context of higher education, with some additional aspects: an increasingly interconnected and diverse world with serious social inclusion problems; the evident need for accountability; and the emergence of innovative models that make the teaching-learning process more complex. The message for university systems seems to be clear, and there is one concept that stands out: innovation.
Keywords: Educación superior; Innovación; Responsabilidad social; Liderazgo y gobernanza; Calidad y acreditación; Sistemas